Keluarga Sebagai Dasar Pendidikan Bagi Anak - M. Nur Kholis Al Amin (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2013)
Abstract: Development is a thing that will happen to human life in its various aspects to complement the needs of human being as individual and social beings. Therefore, necessary to establish religious education human personality perfectli capable of mastering technology and science by sticking to religious doctrines as a measure of ethics in everyday life. However, it will not be separated from the role of the family as an institution beggining in shaping a person’s character. Thus, the formation of one’s character to be the perfect man ( insan kamil) is inseparable from the process of religious education in the family. Keywords : Family, Religious Education, Society.